The Motif of the Tradition of Female Circumcision "Patuk Ayam" in the Bugis Community in Jayapura: Studi Living Hadits - Al Abza, M. Thohar; Muhyidin, Syaiful; Makatita, Ahmad Syarif; Sulha, Sulha (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
The relationship between Islam and the Bugis society is strongly intertwined through traditions that last for generations. One such tradition is makkatteâ€™ or female circumcision â€œpatuk ayamâ€ performed by the Bugis community in Jayapura. This tradition is interpreted as a religious commandment derived from the hadits. This article examines this tradition and its motives from a living hadits perspective to find a correlation between local wisdom and Islamic values. The research employs a descriptive-qualitative method, drawing data from documentation, observation, and interviews within a phenomenological framework. Utilizing Alfred Schutzâ€™s concept of motive in phenomenology, data is categorized based on in-order-to motives and because-of motives. Through verification and substantiation, the results show that the practice of hadits is not only in the practice of circumcision but also combined with the traditional ceremony of validating the Muslim status of a daughter. The symbols of the tradition, including the procession, props, and the clothes to be worn, show the hopes of the parents that their daughters will be religiously observant, avoid misfortune, be hardworking, independent, and easily find a mate. This futuristic expectation is considered to be in line with the values contained in the Prophetic traditions.